Efficacy of Calcipotriol 0.005% Ointment for Uremic Xerosis with Pruritus in Chronic Kidney Diseases Undergoing Hemodialysis Patients: Randomized Double Blind Clinical Trial - Widyastuti; Yulia Farida Yahya; Suroso Adi Nugroho; Soenarto Kartowigno; M. Izazi Hari Purwoko; Irsan Saleh (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Uremic xerosis with pruritus (UXP) is a chronic cutaneous complication among patients undergoing maintenance renal dialysis. Uremic xerosis level is directly related with pruritus severity or vice versa. Uremic xerosis with pruritus may lead to discomfort and negative psychological effect. The ethiopathogenesis still unknown, Most of treatments are empirical, and there is no effective and safe therapy. Emollient has not been effective enough to improve quality of life. There is some report about efficacy of topical vitamin D in xerosis and chronic pruritus. Objective: We evaluate the efficacy of calcipotriol 0.005% ointment for uremic xerosis and uremic pruritus in chronic kidney disease patients undergoing hemodialysis. Material & methode: Sixty two patients with UXP were enrolled, randomized double blind study. Patients were divided to two group, calcipotriol 0.005% ointment group or placebo. In baseline, patients were instructed to apply twice daily for four weeks. We assesesment the efficacy and safety of calcipotriol 0.005% ointment and placebo after 2nd and 4th weeks treatment using overall dry skin score (ODSS), visual analog scale (VAS), corneometer and sebumeter. We also assessed adverse effect and tolerance this drugs using visual assessment scale. Results: Overall dry skin score (ODSS) and visual analog scale (VAS) significantly decreased in calcipotriol 0.005% ointment group than in placebo group (p <0.05). Skin hydration level based on Corneometer score and skin surface lipid based on Sebumeter score was significantly increased in calcipotriol 0.005% ointment group than in placebo group (p <0.05). Cure rate and clinical improvement for calcipotriol 0.005% ointment group was significantly higher than placebo group. There was no adverse effect between two groups after treatment. Conclusion: calcipotriol 0.005% ointment is effective than placebo and can be used as alternative or adjuctive treatment and safe and tolerance for UXP.